Genomics and Antimicrobial Susceptibility of Clinical Pseudomonas aeruginosa Isolates from Hospitals in Brazil - Camargo, Carlos Henrique; Yamada, Amanda Yaeko; Souza, Andreia Rodrigues de; Lima, Marisa de Jesus de Castro; Cunha, Marcos Paulo Vieira; Ferraro, Pedro Smith Pereira; Sacchi, Claudio Tavares; Santos, Marlon Benedito Nascimento dos; Campos, Karoline Rodrigues; Tiba-Casas, Monique Ribeiro; Freire, Maristela Pinheiro; Barretti, Pasqual [UNESP] (MDPI, 2023)
Pseudomonas aeruginosa, an opportunistic pathogen causing infections in immunocompromised patients, usually shows pronounced antimicrobial resistance. In recent years, the frequency of carbapenemases in P. aeruginosa has decreased, which allows use of new beta-lactams/combinations in antimicrobial therapy. Therefore, the in vitro evaluation of these drugs in contemporary isolates is warranted. We evaluated the antimicrobial susceptibility and genomic aspects of 119 clinical P. aeruginosa isolates from 24 different hospitals in Brazil in 2021–2022. Identification was performed via MALDI-TOF-MS, and antimicrobial susceptibility was identified through broth microdilution, gradient tests, or disk diffusion. Whole-genome sequencing was carried out using NextSeq equipment. The most active drug was cefiderocol (100%), followed by ceftazidime–avibactam (94.1%), ceftolozane–tazobactam (92.4%), and imipenem–relebactam (81.5%). Imipenem susceptibility was detected in 59 isolates (49.6%), and the most active aminoglycoside was tobramycin, to which 99 (83.2%) isolates were susceptible. Seventy-one different sequence types (STs) were detected, including twelve new STs described herein. The acquired resistance genes blaCTX-M-2 and blaKPC-2 were identified in ten (8.4%) and two (1.7%) isolates, respectively. Several virulence genes (exoSTUY, toxA, aprA, lasA/B, plcH) were also identified. We found that new antimicrobials are effective against the diverse P. aeruginosa population that has been circulating in Brazilian hospitals in recent years.
Keywords: CAZ-AVI; cefiderocol; fosfomycin; Illumina; MEM-VAR; MLST; polymyxin; whole genome sequencing